Micromechanical imaging of dentin with Brillouin microscopy. (15th March 2020) - Lainović, Tijana; Margueritat, Jérémie; Martinet, Quentin; Dagany, Xavier; Blažić, Larisa; Pantelić, Dejan; Rabasović, Mihailo D.; Krmpot, Aleksandar J.; Dehoux, Thomas
Abstract: The structure of teeth can be altered by diet, age or diseases such as caries and sclerosis. It is very important to characterize their mechanical properties to predict and understand tooth decay, design restorative dental procedures, and investigate their tribological behavior. However, existing imaging techniques are not well suited to investigating the micromechanics of teeth, in particular at tissue interfaces. Here, we describe a microscope based on Brillouin light scattering (BLS) developed to probe the spectrum of the light scattered from tooth tissues, from which the mechanical properties (sound velocity, viscosity) can be inferred with a priori knowledge of the refractive index. BLS is an inelastic process that uses the scattering of light by acoustic waves in the GHz range. Our microscope thus reveals the mechanical properties at the micrometer scale without contact with the sample. BLS signals show significant differences between sound tissues and pathological lesions, and can be used to precisely delineate carious dentin. We also show maps of the sagittal and transversal planes of sound tubular dentin that reveal its anisotropic microstructure at 1 µm resolution. Our observations indicate that the collagen-based matrix of dentine is the main load-bearing structure, which can be considered as a fiber-reinforced composite. In the vicinity of polymeric tooth-filling materials, we observed the infiltration of the adhesive complex into the opened tubules of sound dentine. The ability to probe the quality of this interfacial layer could lead to innovative designs of biomaterials used for dental restorations in contemporary adhesive dentistry, with possible direct repercussions on decision-making during clinical work. Statement of Significance: Mechanical properties of teeth can be altered by diet, age or diseases. Yet existing imaging modalities cannot reveal the micromechanics of the tooth. Here we developed a new type of microscope that uses the scattering of a laser light by naturally-occurring acoustic waves to probe mechanical changes in tooth tissues at a sub-micrometer scale without contact to the sample. We observe significant mechanical differences between healthy tissues and pathological lesions. The contrast in mechanical properties also reveals the microstructure of the polymer-dentin interfaces. We believe that this new development of laser spectroscopy is very important because it should lead to innovative designs of biomaterials used for dental restoration, and allow delineating precisely destructed dentin for minimally-invasive strategies. Graphical abstract: Image, graphical abstract